Using energy psychology to remediate emotional wounds rooted in childhood trauma: preliminary clinical guidelines - Feinstein, David (Frontiers in Psychology, 2023)
Adverse childhood experiences (ACEs) are potentially traumatic events that occur in childhood, such as violence, abuse, severe neglect, or mental health problems in caregivers. The negative physical and mental health consequences of severe or multiple ACEs provide a major challenge for the health care community. Psychotherapies that utilize a mind–body approach in treating ACE-related conditions are seen by their proponents as having advantages for bringing healing and restoration compared with talk, introspective, interpersonal, and exposure therapies that do not intervene at the body level, as famously encapsulated by Bessel van der Kolk’s observation that “the body keeps the score.” A mind–body approach whose use has been rapidly increasing in clinical settings as well as on a self-help basis is called “energy psychology.” Energy psychology combines conventional therapeutic techniques such as cognitive restructuring and psychological exposure with the stimulation of acupuncture points (acupoints) by tapping on them. A review of the development, efficacy, and plausible mechanisms of energy psychology is presented, and several strengths are enumerated, such as how integrating acupoint tapping into conventional exposure methods enhances the speed and power of outcomes. The impact of energy psychology protocols on the three brain networks most centrally involved with ACEs is also examined. Finally, recommendations are offered for using an energy psychology approach at each stage of therapy with individuals who have endured severe or multiple ACES, from establishing a therapeutic alliance to assessment to treatment to follow-up.